1998
DOI: 10.1097/00000658-199808000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ultrasound Enhances Standard Laparoscopy in the Staging of Pancreatic Cancer

Abstract: ObjectiveTo define the role of laparoscopic ultrasound (LUS) in the staging of pancreatic tumors. Summary Background DataLaparoscopy has recently been established as a valuable tool in the staging of pancreatic cancer. It has been suggested that the addition of LUS to standard laparoscopy could improve the accuracy of this procedure. MethodsA prospective evaluation of 90 patients with pancreatic tumors undergoing laparoscopy and LUS was performed over a 27-month period. LUS equipped with an articulated curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(65 citation statements)
references
References 25 publications
3
58
0
3
Order By: Relevance
“…In a cohort of 90 subjects with pancreatic cancer, laparoscopic US concluded the resectability in 13 patients (14%), where laparoscopic analysis alone had led to vagueresults [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of 90 subjects with pancreatic cancer, laparoscopic US concluded the resectability in 13 patients (14%), where laparoscopic analysis alone had led to vagueresults [8].…”
Section: Discussionmentioning
confidence: 99%
“…[8] Moreover, Hunerbein et al [9] stated that laparoscopic US added additional data to laparoscopy in 12% of subjects with pancreatic cancer, who were establish to have resectable disease on preoperative US, CT and MRI. The mixture of SL with US in this work confirmed irresectability in 57% of cases with a consequential change in surgical plan.…”
Section: Discussionmentioning
confidence: 99%
“…The yield of laparoscopy for the detection of metastatic disease, especially of small peritoneal lesions that have not been detected by imaging modalities, ranges from 15 to 46% (Jimenez et al, 2000;Menack et al, 2001;Minnard et al, 1998;Velasco et al, 1998;Liu & Traverso, 2005). Recent studies have shown lower yields for laparoscopy than for improved non invasive imaging modalities like multi detector CT.…”
Section: Laparoscopic Diagnosis/stagingmentioning
confidence: 99%
“…Some have advocated the routine use of laparoscopic ultrasonography to enhance the accuracy of the staging procedure with respect to the primary tumor relationship to the major blood vessels, the presence of enlarged peripancreatic lymph nodes or small deep liver metastasis [5] . In this setting, laparoscopic ultrasonography may identify additional disease in approximately 10% of patients [6,7] but whether it should be routinely or selectively used is controversial. Laparoscopic ultrasound probes are not widely available and thus the surgeon's familiarity with the findings is limited.…”
Section: Laparoscopic Techniquementioning
confidence: 99%